2022
DOI: 10.2174/1573399817666210928144706
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Biomarkers as Predictors of Infected Diabetic Foot Ulcer

Abstract: : Diabetic foot ulcer infection is a crucial complication associated with lower-limb amputation and postoperative mortality in individuals with diabetes mellitus. Deciding if a diabetic foot ulcer is infected in a community setting is challenging without validated point-of-care tests. Early detection of infected diabetic foot ulcers can reduce the frequency of hospitalizations, the occurrence of disability, and chances of mortality. Inflammatory biomarkers are predictors of infected diabetic foot ulcers and lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 82 publications
0
6
0
Order By: Relevance
“…Second, we recognize that other epigenetic enzymes may regulate Mφ function in diabetic wounds and that these enzymes do not work in isolation but rather contribute at different phases of wound repair to the cell phenotype [ 63 65 ]. Third, we realize that IL-6 is unlikely to be the only driver of JAK1,3/STAT3 signaling in wounds, although IL-6 elevation in diabetic wounds is well documented [ 66 , 67 ], and we show that it is persistently elevated in diabetic wound Mφs. Finally, we have not directly examined the interplay between Mφs and other structural cells, such as smooth muscle cells or fibroblasts, that exist within the wound.…”
Section: Discussionmentioning
confidence: 68%
“…Second, we recognize that other epigenetic enzymes may regulate Mφ function in diabetic wounds and that these enzymes do not work in isolation but rather contribute at different phases of wound repair to the cell phenotype [ 63 65 ]. Third, we realize that IL-6 is unlikely to be the only driver of JAK1,3/STAT3 signaling in wounds, although IL-6 elevation in diabetic wounds is well documented [ 66 , 67 ], and we show that it is persistently elevated in diabetic wound Mφs. Finally, we have not directly examined the interplay between Mφs and other structural cells, such as smooth muscle cells or fibroblasts, that exist within the wound.…”
Section: Discussionmentioning
confidence: 68%
“…It is reported 24 that IL‐6 stimulates the inflammatory and autoimmune processes of many diseases, such as diabetes, atherosclerosis, depression, Alzheimer's disease, systemic lupus erythematosus, multiple myeloma, prostate cancer, Behcet's disease, and rheumatoid arthritis. IL‐6 has certain value in the course monitoring of type 2 diabetes patients with foot infection 25 . Therefore, these above research results suggested that TNF‐ α, PCT, and IL‐6 could be used as diagnostic factors of DFU.…”
Section: Discussionmentioning
confidence: 89%
“…IL-6 has certain value in the course monitoring of type 2 diabetes patients with foot infection. 25 Therefore, these above research results suggested that TNF-α, PCT, and IL-6 could be used as diagnostic factors of DFU. In addition, the results of this study showed that the levels of PCT, TNF-α, and IL-6 in the DFU patients with cardiovascular events group were significantly higher than those in the nonoccurrence group, suggesting that abnormal inflammatory response in DFU patients could promote the occurrence of adverse cardiovascular events.…”
Section: Discussionmentioning
confidence: 91%
“…Researchers have been interested in finding the differences between IDFUs and DFUs, and these markers may be suitable for prognostic purposes [31]. Our objective was to identify the differences between above-and below-the-ankle limb amputation, and we found that only WBCs and HbA1c showed significant differences.…”
Section: Discussionmentioning
confidence: 90%